Cone Beam Computerized Tomographic (CBCT) Assessment of Buccal Bone Thickness in Maxillary Aesthetic Region: CBCT: Buccal Bone Thickness in Maxillary Aesthetic Region - Rehmat, Safia; Afridi, Muhammad Humayun; Noreen, Naila; Masood, Farooq; Ashfaq, Hussam Muhammad; Sultana, Saadia (Pakistan Journal of Health Sciences, 2026)
Buccal bone thickness (BBT) in the maxillary aesthetic region is a key determinant of ridge remodeling and the chances of recession of the mucosa following implantation. Objectives: To measure BBT at standardized levels around maxillary central incisors, lateral incisors, and canines on CBCT scans of patients from Peshawar, Pakistan. Methods: This cross-sectional study assessed 96 CBCT scans of patients aged 18–60 years obtained from the Department of Oral and Maxillofacial Radiology, Rehman Medical Institute/Rehman College of Dentistry, Peshawar, over six months from 3 February 2025 to 3 August 2025. BBT was measured on sagittal reconstructions at the crestal level (L0) and at 1 mm (L1), 3 mm (L3), and 5 mm (L5) apical to the crest. Descriptive statistics were reported; gender differences were explored using independent-samples tests and age associations using Spearman correlation (α=0.05). Results: At L0, BBT was <1 mm in 90.6% of central incisors, 90.7% of lateral incisors, and 84.3% of canines. Males showed greater BBT than females at selected levels (central incisors: L1 and L5; lateral incisors: L5). Age showed statistically significant but weak correlations with BBT at L1 for central incisors and at L5 for lateral incisors and canines. Conclusions: In this sample, the buccal plate in the anterior maxilla was predominantly thin (<1 mm), particularly for lateral incisors and at the crest. Preoperative CBCT assessment should guide implant positioning and the anticipated need for augmentation, with consideration of patient sex and age.